A critical analysis of global ecosystem services (Paristhitiki sewa) discourse in Nepal - Chaudhary, Sunita; McGregor, Andrew (Land use policy, 2018)
•We explored how ES discourse is being promoted and interpreted in Nepal.•We carried out content analysis of policies, peer-reviewed articles, reports, media, and conducted in-depth interviews.•International actors are highly influential in promoting the concept and shaping its meaning.•It is primarily interpreted in terms of economic valuation and payments for ecosystem services reflecting the influence of global discourse.•The concept should be contextualised to reflect national priorities rather than complying with international agenda. ‘Ecosystem services’ (ES) is a globalising concept that is being incorporated into environmental policies around the world. It is particularly advanced in Western nations which were active in developing the concept, but less applied in non-Western contexts. In this paper, we explore how the ecosystem services concept is being promoted and interpreted in the context of Nepal. We conducted a content analysis of environmental policies, peer-reviewed articles and media coverage, as well as in-depth interviews with key stakeholders. The findings show that the concept is being increasingly integrated into environmental policy documents and is likely to become influential. International actors are most responsible for supporting the concept in Nepal, primarily through funding projects, shaping the way ecosystem services concept is understood and articulated in the country. ES is primarily constructed in terms of economic valuation and payments for ecosystem services, in particular for forest and water services. The paper discusses the risks that have been associated with the commodification of ecosystem services in the broader literature, such as over extraction of resources, inequitable outcomes, and the marginalisation of intangible benefits that cannot easily be monetarily valued. The study argues that rather than complying with international agendas, a more comprehensive approach to ecosystem services that defines the scope of the concept, the risks and benefits associated with it and contextualises ecosystem services within national priorities and issues is needed in Nepal.